Effect of hand design and object size on the workspace of three-fingered hands. (March 2019) - Hota, Roshan Kumar; Kumar, C.S.
Highlights: An exploration of the design space of a hand-object system has been carried out. Hand designs with finger base far apart give larger workspace for a large object. Hand designs with finger base close together give larger workspace for small object. Contact locations similar to finger base locations give a larger workspace. Longer link-lengths give larger workspace in general. Graphical abstract: Abstract: This paper presents the design exploration of robotic hands so as to achieve maximum precision manipulation workspace. Kinematic workspace of the hand depends on the object being grasped; therefore we refer to the workspace as the hand-object system workspace. We have considered a three-fingered hand and a tripod grasp on a cylindrical object. We discuss the effect of design variation by changing the finger base location and finger link lengths. Fully actuated and under-actuated versions of the hand have been considered. The workspace has been analyzed in terms of kinematic position and orientation workspace. Results show that for fully actuated hand and large object size, hand designs with finger base farther apart give a larger workspace. For small size objects, however, hand designs in which finger bases are closer together give a larger workspace. Under-actuated versions of the hand give a larger workspace for designs with finger base farther apart, for both small and large object size. Longer link lengths give larger workspace in case of both large and small objects.